Organizational Competence for Servitization - Posselt, Tim (Markt- und Unternehmensentwicklung Markets and Organisations, 2018)
Tim Posselt investigates the factors leading to organizational competence for servitization - a key strategic alternative in times of digitalization and globalization -, and analyses the transformation process servitizing firms undergo. He explores the issue through conceptual research and case studies, and identifies the ability to access and leverage customer knowledge as the foundation of successful servitization. The findings provide valuable insight for managers looking to strengthen their service business, and add to literature on servitization and service-dominant logic. Contents Identification of the decisive factors of organizational competence for servitization Evaluation of the change management process for servitization Analysis of customer knowledge management processes Definition of the relationship between servitization and service-dominant logic Target Groups Researchers and students of strategic management and change management with a focus on servitization Executive managers, service managers and innovation managers aiming to extend their service business, management consultants The Author Dr. Tim Posselt received his PhD in economic sciences from the Friedrich-Alexander-University of Erlangen-Nuremberg. He is head of a research group at the Fraunhofer Center for Applied Research on Supply Chain Services in Nuremberg, focusing on business transformation for the digital age.